Status of drinking water quality in western part of the Thar desert, Sindh, Pakistan - Danishwar, Shahab; Shah, Mohammad Tahir; Leghari, Amanullah (Journal of Himalayan Earth Sciences, 1995)
In Thar Desert, which is one of the most densely populated desert of the world, the primary source of water is dug well. Water available from these dug wells is suspected to be unfit for drinking. Samples of water from the western part of Thar desert were analyzed for anions, cations and trace metals. The data show elevated levels indicating hazardous nature of drinking water. Therefore, it is recommended that appropriate measures should be taken for the supply of clean drinking water to the inhabitants of this densely populated desert of the world.